Adsorption/Ion Exchange of Metal ions on Clay Mineral Surfaces - Gyu Kim, Cheol (Asian Journal of Chemistry, 2013)
This research aimed to investigate the removal of metal ions, such as Al3+, Cu2+, Mn2+, Pb2+ and Zn2+, by adsorption or ion exchange on clay minerals. Refined natural bentonite (raw-bentonite), Ca2+ and Na+ ion exchanged bentonite (Ca- and Na-bentonite) and commercial montmorillonite KSF and K10 from Sigma Aldrich, were used. The component of five inorganic clays was analyzed by XRF. The concentration of metal ions was measured by ICP. The cation exchange capacity and the particle charge of clay minerals were measured. The initial concentration range of metal ions was 10-100 ppm. From the experimental results, it was shown that the adsorption equilibrium was obtained within 1-2 h. The maximum percentage removals of Al3+, Cu2+, Pb2+ and Zn2+ on Na-bentonite was more than 98 % and that of Mn2+ was 66 %. Al3+ was leached out from KSF because of increased H+ concentration. In general, the percentage removal of metal ions was decreased with increasing of the initial concentration of metal ions. The adsorption capacity of metal ions was in the order of Na-bentonite >> raw-bentonite @ K10 >Ca-bentonite > KSF. The Freundlich constant (K) of Na-bentonite was the largest for metal ions. The order of Freundlich constant (K) of Na-bentonite on metal ions was Al3+ > Cu2+ > Pb2+ > Zn2+ > Mn2+ and the adsorption intensity (1/n) was determined to be 0.2 to ca. 0.39.